Covid-19 Pandemic And The Adversity Of Hotel Industry: Relationship Between Service Guarantees On Service Quality Perception And Consumer Perceived Risk - OKTAVIO, ADRIE; KARTIKA, ENDO WIJAYA; TARIGAN, ZEPLIN JIWA HUSADA; KAIHATU, THOMAS STEFANUS (The journal of contemporary issues in business and government, 2021)
The impact of the Covid-19 pandemic has been significantly felt by many industries, especially the hotel industry in Indonesia. Declining occupancy had been a significant blow to the industry that also has an impact on the company. Therefore, some policies are taken, such as layoff, temporarily operation suspend, or even permanent termination. Even though the Indonesian government has relaxed its social restriction policy, declining occupancy has still occurred. In other words, consumers are still not sure about the implementation of health protocols in public, including hotels. This study investigates consumer perceived risk influenced by service guarantees and service quality perception during the Covid-19 pandemic condition, retrieving research data from 312 starred-hotel consumers in East Java and Bali provinces. The results showed that service guarantees directly and significantly affect service quality perception and consumer perceived risk. However, service quality perception has a direct effect but not significant on consumer perceived risk.